Дар комптентного признания (к 80-летию Вилена Черноволенко — одного из основоположников социологии в Украине) (Социология: теория, методы, маркетинг, 2009)
This year January 26th was the Vilen Chernovolenko’s eightieth birthday. He is one of the founders of Ukrainian sociology as an academic scientific branch. His career in humanities and social sciences amounts to a half a century of fruitful research, magistral and public activity. Socio-political atmosphere of 1960th assigned him a role of mastermind in the new to Ukraine branch of social knowledge. Institutional for mation of the Ukrainian sociology occurred to a great extent thanks to his efforts. Vilen Chernovolenko is a patriarch of the Kievan academic sociological community, who reared the pleiad of eminent scientists and took part in laying the foundation of traditions which are alive until now. Being quick on the uptake of innovations in development of sociology, he broke new ground of some perspective research trends on the problems of profession prestige, reproduction of brainpower, social and status stratification under conditions of transition to market economy and so on. In the set historical circumstances, Vilen Chernovolenko has never lost an ability of critical mind, the innovative spirit, and democratic style of scientific dialog with his colleagues and progeny.